Ollie the octopus at the office: oxford essential reading - Love, Elizabeth (Oxford University Press South Melbourne, 1999)
"Ollie the Octopus at the Office" follows the adventures of Ollie, a cheerful octopus who brings fun and creativity to a typical office environment. As Ollie navigates the daily routines of the employees, he uses his unique abilities to solve problems and lighten the mood. The story highlights themes of teamwork, imagination, and the importance of a positive work atmosphere. Through Ollie's playful antics, readers learn about collaboration and the joy of bringing a little whimsy to everyday life.